2005
DOI: 10.1007/s00442-005-0099-z
|View full text |Cite
|
Sign up to set email alerts
|

Invasive annual grasses indirectly increase virus incidence in California native perennial bunchgrasses

Abstract: In California valley grasslands, Avena fatua L. and other exotic annual grasses have largely displaced native perennial bunchgrasses such as Elymus glaucus Buckley and Nassella pulchra (A. Hitchc.) Barkworth. The invasion success and continued dominance of the exotics has been generally attributed to changes in disturbance regimes and the outcome of direct competition between species. Here, we report that exotic grasses can also indirectly increase disease incidence in nearby native grasses. We found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
217
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 203 publications
(234 citation statements)
references
References 51 publications
8
217
1
2
Order By: Relevance
“…More generally, the indirect effects on the abundance of one species caused by the presence of a second one mediated by shared pathogens or predators (apparent competition) is recognized as an important factor influencing community dynamics and vegetation patterns (Morris et al 2004). It may account for the invasion success of exotic annual grasses in California Valley grasslands (Malmstrom et al 2005). Conversely, an alternative host could act as a sink, contributing to the decrease in the prevalence in the focal species.…”
Section: Impact Of Landscape Composition On Global Pathogen Propagulementioning
confidence: 99%
“…More generally, the indirect effects on the abundance of one species caused by the presence of a second one mediated by shared pathogens or predators (apparent competition) is recognized as an important factor influencing community dynamics and vegetation patterns (Morris et al 2004). It may account for the invasion success of exotic annual grasses in California Valley grasslands (Malmstrom et al 2005). Conversely, an alternative host could act as a sink, contributing to the decrease in the prevalence in the focal species.…”
Section: Impact Of Landscape Composition On Global Pathogen Propagulementioning
confidence: 99%
“…Although several mechanisms have been suggested to explain the apparent enigma in which an inferior competitor has invaded and remained numerically dominant across much of California for more than a century (e.g., grazing, rainfall changes, and perennial seed limitation; see refs. 10 and 13), disease has only recently been suggested as a potential factor in this invasion (14). Although it has been shown that invasion by annual grasses can increase the prevalence of a viral pathogen (14), there have been no quantitative tests to determine whether these effects could alter the long-term competitive dominance hierarchy of native and exotic grasses in California.…”
mentioning
confidence: 99%
“…10 and 13), disease has only recently been suggested as a potential factor in this invasion (14). Although it has been shown that invasion by annual grasses can increase the prevalence of a viral pathogen (14), there have been no quantitative tests to determine whether these effects could alter the long-term competitive dominance hierarchy of native and exotic grasses in California. Here, we develop a dynamical model that uses field-based parameter estimates to examine whether the invasion by nonnative annual grasses may have altered the long-term community-wide dynamics of a globally distributed generalist virus of grasses, resulting in widespread invasion and persistent domination of the California grassland flora by a suite of otherwise competitively inferior introduced grasses from southern Europe.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7A). The presence of the annual exotic Avena fatua increases spring populations of aphid vectors and leads to the doubling of BYDV incidence in native grasses (79) (Fig. 7B).…”
Section: Community and Ecosystem Ecologymentioning
confidence: 99%